The effectiveness of e-corporate governance in improving the quality of financial information - Imane BENSIRADJ (Journal of Excellence for Economics and Management Research, 2026)
The aim of this study was to fall on the reality of the application of the principles of corporate governance in Algeria, And to highlight the impact of the application of the principles of corporate governance in the activation of the quality of accounting information disclosed, The implications for users of accounting information in making their decisions.      The study focused on the extent to which degree the quality of accounting information after the adoption and application of the principles of corporate governance in the Algerian institutions, And after study shows that the adoption of Applied Corporate Governance in the organization Algerian foaming quality of accounting information (Accuracy, reliability, comparability ...) Which allows planting of trust between all dealers with a private institution investors and lenders, This has a positive impact on the ease of financing and contracting with banks and good to deal with related parties.